Potential of Eucalyptus Species in Insect Pest Management Programme - Kathuria, Vanit; Kaushik, Nutan (Indian Forester, 2005)
The members of genus Eucalyptus (Myrtaceae) are subject of great interest owing to presence of essential oils that are utilized for pharmaceutical or other industrial purposes. Besides this, the biological activity against insect pests has drawn considerable interest. The present review provides a summary of the various studies conducted using Eucalyptus leaf oil, powder and extract revealing its potential for the application in management of insects of agricultural crops.